INSTITUTE OF ENTREPRENEURSHIP IN THE INSTITUTIONAL SPACE OF RUSSIA - S. Sazanova (Вестник университета, 2017)
The article concretizes the content of the concepts «institution of entrepreneurship», «institutional environment», «institutional space» on the basis of methodological approaches of modern new institutionalism, neo-institutionalism, traditional institutionalism and system economic theory. The author outlines key components and features of Russia's institutional space in terms of the level of legality and illegality, value conflict and opportunism. The author reveals the contour of the institution of entrepreneurship in the institutional space of Russia on the basis of defining its borders with the institution of charity, on the one hand, and the institution of criminal activity with the aim of extracting benefits, on the other.